Production of carbon nanotubes and hydrogen by catalytic ethanol decomposition (2013)
This work reports the synthesis of multiwall carbon nanotubes (MWCNTs) by the catalytic decomposition of ethanol using the perovskite-type oxide LaNiO3 as catalyst precursor. The carbon nanotubes were characterized by transmission electronic microscopy (TEM), scanning electronic microscopy (SEM) and thermogravimetric analysis (TGA). TEM micrographs show that the carbon nanotubes were multi-walled with inner diameters ranging from 3 nm to 12 nm and outer diameters up to 42 nm. The yield of CNT and H2 were 3.5 gCNT?(gcat?h)-1 and 39 LH2?(g?h)-1 respectively at 700 °C. TGA data show that nanotube carbon purity was about 95 % by weight and the oxidation temperature was around 620 °C.